2006
DOI: 10.1620/tjem.209.69
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Methylprednisolone Therapy in Type 3 Adenovirus Pneumonia with Hypercytokinemia

Abstract: Adenovirus pneumonia is uncommon but its severe infection has a mortality as high as 10%, and survivors may have residual airway damages, manifested by bronchiectasis, bronchiolitis obliterans, or pulmonary fibrosis. We report a case of adenovirus pneumonia demonstrating fatal respiratory distress. Adenovirus was isolated from pharyngeal specimens using cell culture and typed as serotype 3 by a combination of polymerase chain reaction (PCR) and restriction fragment length polymorphism analysis. The patient cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
10
1
1
Order By: Relevance
“…Takahashi et al reported that use of pulse methylprednisolone (25mg/kg/day) for 3 days, in a case of severe HAdV pneumonia (type 3) with hypercytokinemia i.e raised lactate dehydrogenase, ferritin, interferon-gamma and interleukin-6, resulted in relief of respiratory distress. [ 29 ] He also suggested that serum Krebs von den Lungen-6 (Kl-6) could be used as a marker of future lung disease. Cidofivir is occasionally used in immunocompromised children with severe HAdV.…”
Section: Discussionmentioning
confidence: 99%
“…Takahashi et al reported that use of pulse methylprednisolone (25mg/kg/day) for 3 days, in a case of severe HAdV pneumonia (type 3) with hypercytokinemia i.e raised lactate dehydrogenase, ferritin, interferon-gamma and interleukin-6, resulted in relief of respiratory distress. [ 29 ] He also suggested that serum Krebs von den Lungen-6 (Kl-6) could be used as a marker of future lung disease. Cidofivir is occasionally used in immunocompromised children with severe HAdV.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of corticosteroids on severe HAdV CAP is still uncertain, although there have been a few case reports. One case of a fatal HAdV-3 pneumonia with hypercytokinemia, “pulse” methylprednisolone treatment resulted in the rapid amelioration of the patient’s respiratory distress [29]. In a study focused on severe CAP caused by HAdV-55, 10 out of 18 patients received corticosteroids and total mortality was 5.9% [17].…”
Section: Discussionmentioning
confidence: 99%
“…There have been a limited number of case reports describing adenovirus pneumonia complicated with HLH [2,4,5,6]. In these reports, adenoviral pneumonia with HLH was successfully treated with IVIG and clarithromycin, dexamethasone and cyclosporine, or pulse methylprednisolone [2,4,6].…”
Section: To the Editormentioning
confidence: 99%
“…There have been a limited number of case reports describing adenovirus pneumonia complicated with HLH [2,4,5,6]. In these reports, adenoviral pneumonia with HLH was successfully treated with IVIG and clarithromycin, dexamethasone and cyclosporine, or pulse methylprednisolone [2,4,6]. Antiviral treatment with cidofovir or ribavirin in adenovirus infections is being increasingly used, especially in immunocompromised patients; however, the efficacy of these drugs is not established [7,8].…”
Section: To the Editormentioning
confidence: 99%